Dietary polyphenol and microbiota interactions in the context of prostate health. Issue 1 (11th October 2021) - Piwowarski, Jakub P.; Stanisławska, Iwona; Granica, Sebastian
Abstract: Recent data strongly indicate a relationship between prostate health and gut microbiota, in which composition and physiological function strictly depend on dietary patterns. The bidirectional interplay of foods containing polyphenols, such as ellagitannins, condensed tannins, lignans, isoflavones, and prenylated flavonoids with human gut microbiota, has been proven to contribute to their impact on prostate health. Considering the attributed role of dietary polyphenols in the prevention of prostate diseases, this paper aims to critically review the studies concerning the influence of polyphenols' postbiotic metabolites on processes associated with the pathophysiology of prostate diseases. Clinical, in vivo, and in vitro studies on polyphenols have been juxtaposed with the current knowledge regarding their pharmacokinetics, microbial metabolism, and potential interactions with microbiota harboring different niches of the human organism. Directions of future research on dietary polyphenols regarding their interaction with microbiota and prostate health have been indicated. Abstract : Considering the attributed role of polyphenol‐containing food products in the prevention of prostate diseases, this perspective aims to critically review studies on the influence of polyphenol‐derived postbiotic metabolites produced by gut microbiota on processes associated with prostate pathophysiology and juxtapose them with the current knowledge regarding the role of the microbiome in prostate health and its contribution to the development of prostate diseases.